2023
DOI: 10.3390/su15108137
|View full text |Cite
|
Sign up to set email alerts
|

Online Luxury Resale Platforms and Customer Experiences: A Text Mining Analysis of Online Reviews

Abstract: There are long-standing arguments that challenge the resale business as a circular fashion model. Considering the whole fashion industry and market, luxury resale is still quite small. To scale the industry, it is critical to attract more consumers to embrace fashion resale and circular fashion. However, many of the customers most likely to embrace resale might have already opted into the market, indicating that online or in-store resale businesses are competing for a limited pool of customers. As a result, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…The analysis revealed motivations that exclusively influence selling, buying, and both selling and buying practices (Table 2). Differentiating from previous studies that identified financial benefit and environmental consciousness as factors influencing general consumers [11,32], our study provides a more nuanced explanation of selling and buying motivations.…”
Section: Motivationsmentioning
confidence: 71%
See 4 more Smart Citations
“…The analysis revealed motivations that exclusively influence selling, buying, and both selling and buying practices (Table 2). Differentiating from previous studies that identified financial benefit and environmental consciousness as factors influencing general consumers [11,32], our study provides a more nuanced explanation of selling and buying motivations.…”
Section: Motivationsmentioning
confidence: 71%
“…Firstly, in terms of the characteristics of secondhand items, consumers are motivated to participate in OFRPs by financial gains, unique styles, and the utility of buying or selling pre-owned items [8,30], while the challenges include functional risks, health concerns, and stigmas [21,31]. Secondly, platform-related motivations involve diverse product choices, fast acquisition, and ease of use; challenges include information accuracy, inefficient services, and trust issues with sellers [14,32]. Thirdly, industry-related challenges include regulation issues, authenticity, and internet fraud concerns [17].…”
Section: Consumer Engagement In Ofrps: Motivations and Challengesmentioning
confidence: 99%
See 3 more Smart Citations